2016
DOI: 10.1016/j.scitotenv.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of complex septic odorants in Huangpu River source water by combining the data from gas chromatography-olfactometry and comprehensive two-dimensional gas chromatography using retention indices

Abstract: Identification of the trace odorants causing the septic odors in source waters with complex matrixes has long been a big challenge. The Huangpu (HP) River, an important source water for Shanghai, has long been suffering from septic and musty odors, although major odorants have not been identified. In this study, combining the data from gas chromatography-olfactometry with mass spectrometry (GC-O/MS) and comprehensive twodimensional gas chromatography with time-of-flight mass spectrometry (GC × GC-TOFMS) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…This might be attributed to the masking action of the earthy/musty odor by the strong fishy or rancid/swampy ones. Guo et al (2016) also reported similar results in which relatively high intensity septic/swampy odor caused by dimethyl disulfide and diethyl disulfide suppressed the earthy/musty odor caused by 2-MIB and geosmin. Up to now, Cyanobacteria are the only known producers of 2-MIB and geosmin among algae (Watson, 2010).…”
Section: Evaluation Of Typical Odorous Compoundssupporting
confidence: 53%
“…This might be attributed to the masking action of the earthy/musty odor by the strong fishy or rancid/swampy ones. Guo et al (2016) also reported similar results in which relatively high intensity septic/swampy odor caused by dimethyl disulfide and diethyl disulfide suppressed the earthy/musty odor caused by 2-MIB and geosmin. Up to now, Cyanobacteria are the only known producers of 2-MIB and geosmin among algae (Watson, 2010).…”
Section: Evaluation Of Typical Odorous Compoundssupporting
confidence: 53%
“…The Huangpu (HP) River, an important source water for Shanghai, has long been suffering from complicated odor problems, particularly the septic and musty odors (Sun et al, 2013;Guo et al, 2016). In order to completely abate the odor problem, the O 3 -BAC process has recently been adopted for all of the Water Treatment Plants (WTPs) using HP River source water.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [134,135] and Rong et al [136], used GC×GC-TOFMS to investigate origins of an unpleasant odour in water from different regions in China. Guo et al [134,135] indicated four thioether compounds and ( bis (2-chloroisopropyl) ether) as responsible for swampy/septic odour in the waters from Huangpu and Huai rivers. The authors suggested that 2-methylisoborneol and geosmin are responsible for the musty odour in the first river.…”
Section: Environmentalmentioning
confidence: 99%